A New Genotyping‐in‐Thousands‐by‐Sequencing Single Nucleotide Polymorphism Panel for Mixed‐Stock Analysis of Chum Salmon from Coastal Western Alaska. (9th August 2022) - McKinney, Garrett J.; Barry, Patrick D.; Pascal, Carita; Seeb, James E.; Seeb, Lisa W.; McPhee, Megan V.
Abstract: Genetic stock identification is becoming increasingly important in the management of Chum Salmon Oncorhynchus keta from western Alaska due to frequent run failures in recent times. It has been notoriously difficult to distinguish populations of summer‐run Chum Salmon among four major regions in coastal western Alaska: Norton Sound, lower Yukon River, Kuskokwim River, and Nushagak River. Here we developed and evaluated a panel of single nucleotide polymorphism (SNP) markers designed to coamplify using the genotyping‐in‐thousands by sequencing (GT‐seq) method, which would greatly enhance the efficiency of genotyping samples from baseline populations and from mixed‐stock fisheries or incidental catches. We selected 479 SNPs in 355 amplicons from 30, 000 candidate SNPs for the GT‐seq panel. Evaluations using single‐stock and realistic fishery mixture simulations indicated that the panel was able to satisfactorily distinguish Norton Sound from the other regions to the south but was unable to distinguish among lower Yukon, Kuskokwim, and Nushagak rivers with accuracy >90%. The low degree of population structure among Chum Salmon in this region, described in previous studies and confirmed with tens of thousands of SNPs here, means that genetic stock identification will be inadequate to guide management decisions at the spatial scale desired by stakeholders and fishery managers in the region.